How Coping Combination Affects Innovation Ambidexterity in Business Failure Situations - Chen, Jinliang; Jiang, Feng; Lin, Song (Frontiers in Psychology, 2020)
As an effective cognitive and behavioral strategy, coping helps to overcome the negative events. Although coping and its effects have been widely studied in psychology, little is known about the combination of entrepreneurs’ coping and its connection with firms’ innovation ambidexterity. To fill these gaps, in this study, the authors collected 106 samples from two serial-wave surveys of the Bohai Economic Rim in China, tested the theoretical hypotheses using polynomial regression with response surface analysis. The results showed that alignment coping combination enhanced innovation ambidexterity by reshaping an entrepreneur’s cognitive structure. Misalignment coping combination was found to enhance innovation ambidexterity by eliciting entrepreneur’s different types of information processing system. This study contributes to the literatures of the coping, innovation ambidexterity and upper echelons theory from the entrepreneurial cognition approach.